2020
DOI: 10.3390/ma13020481
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Golden Yogurts. Food as a Potential Nanomedicine Carrier

Abstract: Yogurt is one of the most emblematic and popular fermented foods. It is produced by the fermentation of milk lactose by bacteria such as Streptococcus thermophilus and Lactobacillus acidophilus. Magnetic (MNPs) and gold nanoparticles (AuNPs) were incorporated into the exopolysaccharides (EPSs) of these bacteria. The functionalized bacteria were characterized by UV-vis spectroscopy and transmission electron microscopy. A large number of MNPs and AuNPs were bound to the bacterial EPS. Interestingly, the nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The oral iron supplement, including iron fortified formula milk, has been widely studied in infants and children. [ 47 ] In most conditions, the oral iron supplement has been shown to reduce anemia. [ 48 ] However, side effects of oral iron supplement have been reported such as diarrhea and intestinal inflammation under conditions of disease burden.…”
Section: Resultsmentioning
confidence: 99%
“…The oral iron supplement, including iron fortified formula milk, has been widely studied in infants and children. [ 47 ] In most conditions, the oral iron supplement has been shown to reduce anemia. [ 48 ] However, side effects of oral iron supplement have been reported such as diarrhea and intestinal inflammation under conditions of disease burden.…”
Section: Resultsmentioning
confidence: 99%
“…AuNR-bacteria and AuNPR-bacteria were collected at 100 g for 20 min and characterized by UV-vis spectroscopy (using a Thermo Spectronic Unicam UV 300 spectrophotometer), TEM, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and energy-dispersive X-ray spectroscopy (EDX) as previously reported. 35 …”
Section: Methodsmentioning
confidence: 99%
“…AuNR-bacteria and AuNPR-bacteria were collected at 100g for 20 min and characterized by UV-vis spectroscopy (using a Thermo Spectronic Unicam UV 300 spectrophotometer), TEM, highangle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and energy-dispersive X-ray spectroscopy (EDX) as previously reported. 35 2.8 Simultaneous grafting of MNP and AuNPR to the bacteria To incorporate both MNP and AuNPR onto the bacterial surface, 33.3 µL of 0.95 M MNP were mixed with 2 mL of AuNPR colloidal solution and stirred until the mixture was homogenized. A 10 mL aliquot of a Lf culture was collected and centrifugated at 3000g for 10 min.…”
Section: Grafting Gold Nanoparticles To the Bacteriamentioning
confidence: 99%
“…The results indicated that magnetite nanoparticles proved to be an effective supplement in the treatment of iron deficiency anemia. 160 (iv) TiO 2titanium oxide components are used in the food industry as brightening substances. Animal studies indicated that titanium oxide nanoparticles accumulated in mammalian tissues.…”
Section: Food and Function Reviewmentioning
confidence: 99%